Cortical regulation of sleep - Krone, LB (2021)
Sleep is vital but the regulation of sleep is poorly understood. Over the past decades, several subcortical regions in the mammalian brain have been identified, which promote wakefulness or sleep and constitute a ‘sleep switch’. The neurophysiology of the circadian clock, with the suprachiasmatic nucleus of the hypothalamus at its centre, has also been elucidated. However, it is still unclear how the brain tracks the accumulating sleep debt during wakefulness and adjusts the duration and intensity of sleep accordingly. This core process of sleep regulation, termed ‘sleep homeostasis’, remains enigmatic. The cortex engages in characteristic oscillations during sleep that serve as electroencephalographic (EEG) markers of rapid eye movement (REM) and non-rapid eye movement (NREM) sleep. Slow waves, the hallmark of NREM sleep, indicate the depth of sleep and are used to determine the level of the homeostatic process. The aim of my DPhil project was to probe in mice whether cortex, and in particular neocortical layer 5 pyramidal neurons, contribute to the regulation of slow waves and sleep.